Effectiveness of pedicle screw inclusion at the fracture level in short-segment fixation constructs for the treatment of thoracolumbar burst fractures: a computational biomechanics analysis. Issue 13 (3rd October 2017) - Elmasry, Shady; Asfour, Shihab; Travascio, Francesco
Abstract: When treating thoracolumbar burst fractures (BF), short-segment posterior fixation (SSPF) represents a less invasive alternative to the traditional long-segment posterior fixation (LSPF) approach. However, hardware failure and loss of sagittal alignment have been reported in patients treated with SSPF. Including pedicle screws at the fracture level in SSPF constructs has been proposed to improve stiffness and reliability of the construct. Accordingly, the biomechanical performance of the proposed construct was compared to LSPF via a computational analysis. Pedicle screws at fracture level improved the performance of the short-segment construct. However, LSPF still represent a biomechanically superior option for treating thoracolumbar BF.